Marine Sponge is a Promising Natural Source of Anti-SARS-CoV-2 Scaffold - Hamoda, Alshaimaa M.; Fayed, Bahgat; Ashmawy, Naglaa S.; El-Shorbagi, Abdel-Nasser A.; Hamdy, Rania; Soliman, Sameh S. M. (Frontiers in Pharmacology, 2021)
The current pandemic caused by SARS-CoV2 and named COVID-19 urgent the need for novel lead antiviral drugs. Recently, United States Food and Drug Administration (FDA) approved the use of remdesivir as anti-SARS-CoV-2. Remdesivir is a natural product-inspired nucleoside analogue with significant broad-spectrum antiviral activity. Nucleosides analogues from marine sponge including spongouridine and spongothymidine have been used as lead for the evolutionary synthesis of various antiviral drugs such as vidarabine and cytarabine. Furthermore, the marine sponge is a rich source of compounds with unique activities. Marine sponge produces classes of compounds that can inhibit the viral cysteine protease (Mpro) such as esculetin and ilimaquinone and human serine protease (TMPRSS2) such as pseudotheonamide C and D and aeruginosin 98B. Additionally, sponge-derived compounds such as dihydrogracilin A and avarol showed immunomodulatory activity that can target the cytokines storm. Here, we reviewed the potential use of sponge-derived compounds as promising therapeutics against SARS-CoV-2. Despite the reported antiviral activity of isolated marine metabolites, structural modifications showed the importance in targeting and efficacy. On that basis, we are proposing a novel structure with bifunctional scaffolds and dual pharmacophores that can be superiorly employed in SARS-CoV-2 infection.